2013
DOI: 10.1007/s11832-013-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic parameters improve lower extremity prosthetic alignment

Abstract: Purpose The goal of prosthetic fitting is to provide comfort and functionality to the patient. It is thought that incorporating the use of standing anterior-posterior long leg radiographs (LLR) into the fitting of lower extremity prostheses will provide an objective guide when making adjustments, and be a better assessment of alignment. This study compares prosthetic alignment before and after radiography-guided adjustments. Method This retrospective study was performed at a multidisciplinary amputee clinic on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Socket reaction moments and ground reaction forces have been found to be some of the notable factors that indicate misalignment [9]. Other studies have established that radiographic parameters and gait or temporal parameters can also serve as important factors for guiding alignment [10] [11]. Hence, instead of using a system that relies on parameters such as visual inspection, experience, and skill of the prosthetist, more pronounced and effective methods can be devised to capture motion and align a prosthesis.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Socket reaction moments and ground reaction forces have been found to be some of the notable factors that indicate misalignment [9]. Other studies have established that radiographic parameters and gait or temporal parameters can also serve as important factors for guiding alignment [10] [11]. Hence, instead of using a system that relies on parameters such as visual inspection, experience, and skill of the prosthetist, more pronounced and effective methods can be devised to capture motion and align a prosthesis.…”
Section: List Of Tablesmentioning
confidence: 99%
“…The rest of the studies [20][21][22] aligned the prosthesis at the bench before the walking trials, and 1 study did not state. 24 In the primary studies, although 10 m of self-selected walking speed for amputees to adapt alignment changes between trials was considered, adaptation time for 19 studies was not reported. The rest of the studies offered an adaptation time ranging from 5 to 30 min, 25,26,29 one study checked the prosthetic alignment after 1 month, 21 and another followed up monthly for 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…17,18,[28][29][30]37,42,45,47,50,54,62,68,70,78,79 Of the studies that relied on the prosthetist's judgment, eight included supplemental verbal or written patient report. 26,39,43,49,52,56,58,69 No study solely depended on patient report, contrary to assessments of socket fit. All the studies assessing alignment parameter with patient feedback included a second quantitative clinical outcome, such as gait analysis (n 5 2) or smart pyramid-reported socket reaction moments (n 5 2).…”
Section: Measures Of Alignmentmentioning
confidence: 99%
“…Additional alignment parameters used include alignment jig (n 5 4) 57,61,65,74 and radiographic comparison (n 5 1). 56…”
Section: Measures Of Alignmentmentioning
confidence: 99%